Differences in efficacy of two commercial 0.2% chlorhexidine mouthrinse solutions: a 4-day plaque re-growth study - Nicole B. Arweiler (journal of clinical periodontology)
Background: The purpose of this clinical cross-over study was to examine the antibacterial and plaque-inhibiting properties of two chlorhexidine solutions compared with a negative control. Material and Methods: Twenty-one volunteers refrained from all oral hygiene measures, but rinsed instead twice daily with 10 ml of a conventional chlorhexidine solution (0.2%; CHX), a chlorhexidine solution with anti-discolouration system (ADS) (0.2%, alcohol-free chlorhexidine solution (CSP)) or a placebo solution (Pla). Plaque index (PI), plaque area (PA) and bacterial vitality were assessed after 24 h (PI1, vital flora (VF)1) and 96 h (PI2; VF2, PA). After a 10-day wash-out period, a new test cycle was started. Results: Results for Pla were 0.94, 1.59, 27.4 (PI1, PI2, PA) and 79% and 72% (VF1 and VF2). CSP significantly reduced the parameter PI1, PI2 and PA to 0.67 (p50.012), 1.0 and 15.7 (po0.001). VF1 and VF2 (63% and 53%) were not significantly affected. The corresponding figures of CHX were 0.42, 0.43, 6.77, 33 and 16%, which were all significantly lower (all po0.001). On comparing the two chlorhexidine solutions, CHX showed significantly higher reductions of all parameters. Conclusion: The results suggest that the 0.2% alcohol-containing solution showed superiority in inhibiting plaque re-growth and reducing bacterial vitality compared with the solution with ADS.